Zasada domniemania niewinności a ponowne popełnienie przestępstwa przez skazanego: [The presumption of innocence and re-committing the crime by the offender] (Studia Prawnicze / The Legal Studies, 2010)
Celem niniejszego artykułu jest przedstawienie kilku uwag na temat możliwości zastosowania wobec skazanego negatywnych konsekwencji prawnych wynikających z regulacji zawartych w k.k. i k.k.w., na podstawie domniemania ponownego popełnienia przez niego przestępstwa w okresie próby. Ustawodawca, bowiem w art. 68 § 2 i 3 k.k., art. 75 § 2 i 3 k.k., art. 97 § 2 k.k., art. 156 § 1 i 3 k.k.w. i art. 160 § 2 k.k.w., które zawierają przedmiot niniejszego opracowania, nie wprowadził wymogu wydania w pierwszej kolejności wobec skazanego prawomocnego wyroku skazującego, a tym samym przesądzającego jego sprawstwo. Z uwagi na obowiązującą od czterdziestu lat, wyrażoną expressis verbis, zasadę domniemania niewinności, taki stan rzeczy nie powinien mieć racji bytu. Niniejszy artykuł ma być zatem próbą udzielenia odpowiedzi na pytanie czy dopuszczalnym jest, aby zasada domniemania niewinności jako zasada wzruszalna, mogła być obalona w inny sposób, aniżeli przez wydanie prawomocnego wyroku skazującego. The purpose of this article is to present a few observations on the possibility of the using negative legal consequences against sentenced person arising from the regulations contained in the Penal Code and the Executive Penal Code based on presumption of re-committing by him a crime during the trial. The legislature, as in the Article. 68 § 2 and 3 of Penal Code., Art. 75 § 2 and 3 of Penal Code., Art. of Penal Code. 97 § 2, Art. 156 § 1 and 3 of Executive Penal Code and Art. 160 § 2 of the Executive Penal Code which include the subject of this article did not introduce the requirement to release firstly for prisoner final conviction thus prejudging his perpetration. On account of the past forty years expressed in “expressis verbis” principle of presumption of innocence such state of affairs should have no raison d’être. This article is, therefore, an attempt to answer the question whether it is acceptable to the presumption of innocence as a principle of rebuttal could be disproved in other way than through the issuance of a final conviction. This principle has the aim to protect certain values and rights that everyone is entitled, by the same reason that he is a human being. Such rights, which protect the presumption of innocence are: right to liberty, right to a fairand reliable trial, right to dignity and the right to silence. The presumption of innocence is also designed to protect the defendant from incurring its negative consequences of reproaching of the crime he committed. It is here only for the consequences, that arise from the recognition of someone guilty of committing the alleged crime. The accused, therefore cannot experience crime repression characteristic for convicted person for penalty described in art. 32 of Penal Code or for punitive measures mentioned in art. 39 of Penal Code. Nevertheless in Penal Code and in Executive Penal Code we can find regulation that allows drawing for convicted person negative consequences in connection with accusing committing a crime by him during the trial or applied to him temporary detention. These are obviously in most regulations dealing with the optional use by court described institutions however, granting to the judicial authorities applying regulations that may reconcile with presumption of innocence can face into question the reliability of the entire criminal process and can be understood by keeping the process respecting low and freedom of the sites participating in it. By placing in Penal Code regulations art. 68 § 2 and 3, 75 § 2, 97 § 2 and Executive Penal Code. Article. 156 § 1 and 3 and 160 § 2 sentenced is deprived of certainty about his future and stability of the low in the case of reproaching him committing a crime or applied to him temporary detention during the trial connected with for example conditional discontinuance of criminal proceedings. Stability should in fact be based on convinced that it was only at a final finding of guilt of the accused in connection with the re-committing a crime by him he will bear negative consequences of legal in form such as: ordinance enforcement or revocation of conditional early release to serve the remainder of sentence. Meanwhile, despite the principle of presumption of innocence, the legislature allows for the existence of regulations that directly lead to violations of the rule, which is the foundation of the entire criminal process.